Extrinsic compression of popliteal artery in asymptomatic athlete and non-athlete individuals - A comparative study using duplex scan (color duplex sonography) - De Almeida, M. J.; Yoshida, Winston Bonetti [UNESP]; Habberman, D.; Medeiros, E. M.; Giannini, M.; De Melo, N. R. (Edizioni Minerva Medica, 2004)
Aim. Extrinsic compression of the popliteal artery and absence of surrounding anatomical abnormalities characterize the functional popliteal artery entrapment syndrome (PAES). The diagnosis is confirmed to individuals who have typical symptoms of popliteal entrapment and occlusion or important stenosis of the popliteal artery with color duplex sonography (CDS), magnetic resonance imaging (MRI) or arteriography during active plantar flexion-extension maneuvers. However, variable result findings in normal asymptomatic subjects have raised doubts as to the validity of these tests. The purpose of this study was to compare the frequency of popliteal artery compression in 2 groups of asymptomatic subjects, athletes and non-athletes.Methods. Forty-two individuals were studied. Twenty-one subjects were indoor soccer players, and 21 were sedentary individuals. Physical activity was evaluated through questionnaires, anthropometric measurements, and cardiopulmonary exercise test. Evaluation of popliteal artery compression was performed in lower limbs with CDS, ankle-brachial index (ABI) measurements and continuous wave Doppler of the posterior tibial artery.Results. The athletes studied fulfilled the criteria of high level of physical activity whereas sedentary subjects met the criteria of low level of activity. Popliteal artery compression was observed with CDS in 6 (14.2%) studied subjects; 2 of whom (4.7%) were athletes and 4 (9.5%) were non-athletes. This difference was not statistically significant (p=0.21). Doppler of the tibial arteries and ABI measurements gave good specificity and sensibility in the identification of popliteal artery compression.Conclusion. The frequency of popliteal artery compression during maneuvers in normal subjects was 14.2% irrespective of whether or not they performed regular physical activities. Both Doppler and ABI showed good agreement with CDS and should be considered in screening popliteal arteries in individuals suspected of PAES.
Keywords: popliteal artery; functional entrapment syndrome, diagnosis ultrasonography; Doppler; color